1994
DOI: 10.1007/bf00024141
|View full text |Cite
|
Sign up to set email alerts
|

The role of natural agents in the removal of coat-imposed dormancy in Dichrostachys cinerea (L.) Wight et Arn. seeds

Abstract: AbstractsDichrostachys cinerea seeds are impermeable to water and do not germinate readily . The plant, however, contributes to a bush encroachment problem, minimising visibility in wildlife reserves and reducing the area available for grazing . Natural dormancy-breaking conditions must therefore exist, promoting the germinability of these normally dormant seeds . Diurnal temperature fluctuations (50'C/15°C), especially when combined with moisture were found to break dormancy . High temperatures, such as those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
0
13
1
Order By: Relevance
“…However, the seed coat fracture as a result of fire and the following germination depend on the fire's intensity (temperature, duration) and on the species of seed. Conversely, some studies indicated the negative impact of fire on seed germination while others reported minimal or no effect (Brown, 1993;Van Staden et al, 1994). Thus, the questions are: i) do different hard-seeded legume species have the same response to heat shock?…”
Section: Discussionmentioning
confidence: 99%
“…However, the seed coat fracture as a result of fire and the following germination depend on the fire's intensity (temperature, duration) and on the species of seed. Conversely, some studies indicated the negative impact of fire on seed germination while others reported minimal or no effect (Brown, 1993;Van Staden et al, 1994). Thus, the questions are: i) do different hard-seeded legume species have the same response to heat shock?…”
Section: Discussionmentioning
confidence: 99%
“…A relatively high proportion of empty and insect-damaged seeds contributed to this low success. However, unlike A. altissima and U. pumila, R. pseudoacacia seeds present dormancy, which can be broken by natural processes, such as the passage through the digestive track of animals, fires, or abrasion with soil particles [64]. Even if dormancy depresses germination success of a seed cohort in the short term, at longer time scales it may increase reproductive success by extending the temporal window for germination [22].…”
Section: International Journal Of Ecologymentioning
confidence: 99%
“…The seeds of D. cinerea are impermeable to water and dormant at release (van Staden et al 1994b;Witkowski and Garner 2000). Dormancy is mainly broken through diurnal temperature fluctuations, by scarification through ingestion and by bruchid exit holes (van Staden et al 1994b …”
Section: Study Sitementioning
confidence: 99%
“…Fire may additionally promote the regeneration of woody plant species by promoting the release and germination (Brown and van Staden 1997;Keeley and Fortheringham 2000;Brown et al 2003) of seeds. Consumption of seed pods followed by defecation of intact seeds by browsers can also promote shrub recruitment (Brown and Archer 1987;Reyes et al 1994) as scarification through ingestion is known to break seed dormancy (van Staden et al 1994b). On the other hand, large herbivores can inhibit tree establishment directly through browsing, uprooting or trampling of seedlings (Dublin et al 1990;Mwalyosi 1990;Sinclair 1995).…”
Section: Introductionmentioning
confidence: 99%